Studi Fenomenologi: Pengalaman Koping Pada Pasien Kanker Serviks - Hernandia Distinarista (Jurnal Ilmu Keperawatan Maternitas, 2019)
A cancer diagnosis not only affects patients but also family and friends. It is not uncommon for patients to feel anxious, scared and stressed when they hear the word "cancer" when the doctor presents the results of his analysis. Each patient will respond differently and each will handle it in a different way and this is determined by the coping mechanism of the individual. Cancer patients need information, service, and care professionals in order to lead a quality life. This study was designed to explore coping experiences in cervical cancer patients. This study used a hermeneutic phenomenology method, involving five participants in Central Java Province. Data retrieval is done by semi-structured interviews which are then carried out by data transcription. Data analysis using content analysis. In this study, there were two themes, namely adaptive coping and adaptive mall coping. The results of this study indicate that cancer patients need support from the closest person, family and health workers to have adaptive coping during treatment.